Sacred weeds: common ritual plants from the urban botánicas of Miami-Dade County, Florida - Herrera, Barbara; Franck, Alan R.; Rockwell, Cara A. (Ethnobotany Research and Applications, 2021)
Background: Practitioners of syncretic religions often incorporate plants into their sacred rituals, a unique practice that helps keep them connected to their cultural history. An important example of ritual plant use is found in the botánicas (religious stores that cater to practitioners of Afro-Caribbean diaspora religions) of Miami-Dade County, Florida (USA). Methods: We examined ritual plants sold in a sample of six botánicas in Miami-Dade County from November 2018 until April 2019. We addressed the following questions: 1) What is the ratio of native to non-native plant species found in the botánica stores; 2) What is the ratio of invasive exotic to non-invasive exotic plant species found in the botánica stores; and 3) What is the geographical origin of plant species found in the botánica stores? Results: Given the study’s location in South Florida, the frequency of local native flora sold as ritual plants was significantly smaller than initially predicted (27% vs. 65%). Likewise, actual frequency of invasive species was much higher than the expected frequency (32% vs. 19%). We also discovered that most of the taxa collected during the study were Neotropical (50%) and Asian (25%) in origin, while very few African taxa were documented (7 out of the 93 species identified). Conclusion: These botánicas highlight the reliance of Afro-Caribbean syncretic religions in Miami-Dade County on locally common plants, particularly those taxa from the Neotropics. Future studies should further investigate how these plants are being cultivated, traded, and used by the informal economy associated with urban botánicas. Keywords: African diaspora, economic botany, ethnobotany, medicinal plants, religious syncretis